Penerapan CMMI Pada Perusahaan Kecil: Studi Kasus PT. Logix System Technology - Hakim, Abdul Barir (I-STATEMENT: Information System and Technology Management, 2015)
PT. Logix System Technology is a foreign investment company (PMA) that performs software implementation and software development in manufacturing industry. According to the number of staffs, this company is categorized as a small company. The company has been finding problems in delivering product to customers. Management wants to improve performance of the delivery process and solve the problems by adopting Capability Maturity Model Integration (CMMI).The implemetation of CMMI for PT. Logix System Technology is the theme of this research. Products of the research are weaknesses in current running processes of PT. Logix System Technology and their recommended solutions according to CMMI guide. To achieve the desired results, this research has been conducted the following steps: literature studies, data collection by means of direct interview, and analysis. Continuous representation model and CMMI Roadmap have been selected. Assessment was performed by applying appraisal steps in Standard CMMI Appraisal Method for Process Improvement (SCAMPI) C. The results are lists of weaknesses of the current running process and their recommended solutions according to CMMI. These results can be used by PT. Logix System Technology to improve their processes.